INTELLIGENT CONVERSATIONAL MODEL FOR MENTAL HEALTH WELLNESS - Ashish U Mandayam , Siddesha S , S K Niranjan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Mental Health affects how we think, feel and act. Mental Health Problems (MHP) affect our thinking, behavior and mood. The Conversational Model which is being proposed for MHP is an AI based model for slight to moderate measurement users who have MHP like depression, mental stress. The learning techniques used in this work is a neural framework exhibit for setting up the model to give activities and solutions for the users. Here, we are using NLTK for Python to analyse text. The human responses are captured by designing an intelligent engine. The dataset used to train this neural framework is designed and curated under the supervision of psychologists. Here the model helps people with light to moderate level of MHPs by giving simple and easy to perform activities and solutions for their appropriate problems. The model identifies particular phrases which is matched with the data corpus and helps providing appropriate solutions for that particular problem. The Data Corpus has been developed under the guidance of Psychiatrists to help users with MHPs. The user must pass a preliminary test before getting access to the Chat bot